NGF and P75NTR gene expression is associated with the hepatic fibrosis stage due to viral and non-viral causes. - Ednelza da Silva Graça Amoras; Samara Tatielle Monteiro Gomes; Felipe Bonfim Freitas; Bárbara Brasil Santana; Geraldo Ishak; Marialva Tereza Ferreira de Araújo; Sâmia Demachki; Simone Regina Souza da Silva Conde; Marluísa de Oliveira Guimarães Ishak; Ricardo Ishak; Antonio Carlos Rosário Vallinoto (PLoS ONE, 2015)
This study evaluated the relative mRNA expression levels of nerve growth factor (NGF) and the p75 neurothrophin receptor (p75NTR) in different histological stages of human liver disease. Fifty-one liver biopsy specimens obtained from patients with hepatitis B virus (n = 6), hepatitis C virus (n = 28), and non-viral hepatitis--(n = 9) and standard histological liver (n = 8) as controls (CT) were subjected to qPCR and histopathological exams. Our data revealed a significant difference in the NGF expression levels between the three patient groups and the Control group. p75NTR expression levels in the HCV and NVH groups were higher than those observed in the HBV and Control groups. In cases of liver cirrhosis, higher p75NTR mRNA expression was observed, whereas NGF was expressed at higher levels in patients with hepatic fibrosis. NGF expression was lower in the F1 liver fibrosis stage, and p75NTR receptor expression continuously and proportionately increased compared to the increase in the degree of fibrosis and was significantly higher in livers in fibrosis stages 3 and 4. The hepatic levels of NGF and p75NTR were decreased and increased, respectively, relative to the stage of inflammatory activity. A positive correlation between p75NTR and NGF gene expression was observed in livers with mild to moderate fibrosis, though not in cases of severe fibrosis and cirrhosis. Conclusion: Our results demonstrate that the course of chronic liver disease can be regulated by NGF and p75NTR, which function by decreasing or inhibiting hepatocyte regeneration and proliferation.